Perpustakaan dalam pelestarian warisan budaya di Indonesia tinjauan literatur sistematis - Septa Septa; Tamara Adriani Salim (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. Libraries as information institution serves users by collecting, managing and disseminating information and knowledge. One of the important is by preserving cultural heritage. This study aims to describe role of libraries in preserving cultural heritage through publication of scientific articles on the topic of cultural heritage. Data Collection Methods. The paper used a systematic literature review with a qualitative approach. Data Analysis. Several stage involved in data analysis included planning, implementinging, and synthesising the search results Results and Discussion. Findings indicate there are seven selected journal articles discussing policies as obstacles in the preservation of cultural heritage and there are five articles containing the role of libraries focusing on physical form and public education. Conclusion. Based on the selected scientific journal articles describing the role of libraries in Indonesia in preserving cultural heritage, the topics focuses on education for community, procurement, maintenance of physical buildings, ancient manuscripts collections and cultural themes. Furthermore,constraints and challenges faced by libraries,including policies, create an impact on human resources, budget and infrastructure.